How woodcocks produce the most brilliant white plumage patches among the birds. Issue 200 (1st March 2023) - Dunning, Jamie; Patil, Anvay; D'Alba, Liliana; Bond, Alexander L.; Debruyn, Gerben; Dhinojwala, Ali; Shawkey, Matthew; Jenni, Lukas
Abstract : Until recently, and when compared with diurnal birds that use contrasting plumage patches and complex feather structures to convey visual information, communication in nocturnal and crepuscular species was considered to follow acoustic and chemical channels. However, many birds that are active in low-light environments have evolved intensely white plumage patches within otherwise inconspicuous plumages. We used spectrophotometry, electron microscopy, and optical modelling to explain the mechanisms producing bright white tail feather tips of the Eurasian woodcock Scolopax rusticola . Their diffuse reflectance was approximately 30% higher than any previously measured feather. This intense reflectance is the result of incoherent light scattering from a disordered nanostructure composed of keratin and air within the barb rami. In addition, the flattening, thickening and arrangement of those barbs create a Venetian-blind-like macrostructure that enhances the surface area for light reflection. We suggest that the woodcocks have evolved these bright white feather patches for long-range visual communication in dimly lit environments.